Spell bound : a Hex Hall novel - Hawkins, Rachel, 1979- (New York : Hyperion, 2012)
Just as Sophie Mercer has come to accept her magical powers as a demon, the Prodigium Council strips them away and leaves her alone, defenseless, and at the mercy of her enemies the Brannicks, a family of warrior women who hunt down the Prodigium.
Keywords: Demonology -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Paranormal fiction